STRATEGI KOMUNIKASI PEMASARAN KOPI KENANGAN MELALUI KONTEN INSTAGRAM DALAM MENARIK PERHATIAN GENERASI Z PADA GERAI DUREN SAWIT - Shafiqah Hermansyah; Flora Meliana Siahaan (STKIP Subang, 2026)
The rapid development of social media has transformed the way companies build marketing communication with consumers. Instagram has become one of the digital platforms widely used by businesses, including Kopi Kenangan, to deliver product information, promotional messages, and establish relationships with their target audience, particularly Generation Z. This study aims to examine Kopi Kenangan's marketing communication strategy through Instagram content in attracting the attention of Generation Z at the Duren Sawit outlet. This research employed a qualitative approach using a descriptive research design within a constructivist paradigm. Data were collected through in-depth interviews, observation of Kopi Kenangan's official Instagram account, and documentation. Informants were selected using purposive sampling, consisting of Generation Z individuals who actively use Instagram, follow Kopi Kenangan's official Instagram account, and have purchased Kopi Kenangan products. Data were analyzed using the Miles, Huberman, and Saldaña model, including data condensation, data display, and conclusion drawing and verification. The findings indicate that Kopi Kenangan's marketing communication strategy successfully attracts the attention of Generation Z through appealing visual content, clear message delivery, communication style that matches the characteristics of the audience, creative content that follows social media trends, and relevant promotional content. Furthermore, Reels content was perceived as more effective in capturing attention because it is interactive, informative, and provides a more engaging product presentation. The study concludes that Kopi Kenangan's marketing communication strategy implemented through Instagram content aligns with the Attention stage of the AIDA model in attracting Generation Z toward the brand and its products.